BEYOND A PRICING ANOMALY: A SIGNALING PERSPECTIVE ON GREENIUM AS A FINANCIAL INCENTIVE FOR CORPORATE ESG ADOPTION: A SYSTEMATIC LITERATURE REVIEW - Lusiawati Lusiawati; Sri Indarti; Lailan Tawila Berampu; Samsir (Jurnal Al-Iqtishad, 2026)
This study aims to map the development of the greenium literature and examine the shift in research focus from pricing dynamics toward its implications for corporate sustainability practices. This study employs a systematic literature review combined with bibliometric analysis, specifically co-word analysis using VOSviewer. Following the PRISMA 2020 guidelines, this review analyzes peer-reviewed journal articles published between 2020 and 2025. The selected studies are examined using a structured coding framework that captures greenium measurement methods, ESG adoption proxies, moderating factors, and methodological rigor. The findings indicate that the greenium literature is still largely dominated by studies on green bond pricing and yield spreads. Nevertheless, an emerging body of research has begun to link greenium with sustainable finance and corporate ESG, although these connections remain limited and insufficiently integrated. The results suggest that greenium has the potential to function as a financial incentive for corporate ESG adoption; however, empirical evidence regarding its practical impact remains scarce. This study calls for a shift in future research agendas from pricing-focused analyses toward evaluating the role of greenium in fostering substantive corporate sustainability practices.